Current Mapping on the UBS Surabaya Office Building Construction Project - Nuciferani, Felicia Tria; Yudhatama, Putra Tri; Septiarsilia, Yanisfa; Putra, Kurnia Hadi (Faculty of Civil Engeneering and Planning - ITATS, 2023)
In the world of construction, waste is one of the factors that must be minimized or eliminated, because it can cause cost losses and time delays in the implementation of a construction project. Lean production concept approach using Value Stream Mapping (VSM) tools is a method that can be used to minimize waste that can be seen through value-added activities, non-value added but necessary. The scope of work that has a significant impact on the UBS Surabaya office building construction project consists of ironwork, concrete work, and formwork work on the superstructure, during the period from March to May 2021. In the scope of work identified Value Added amounting to 73 activities (61.34%), and Non-Value Added but Necessary totaling 26 activities (21.85%). There are several types of waste that occur during the implementation process,